PERAN KEPEMIMPINAN SITUASIONAL DALAM KONSEP INTEGRASI MADRASAH DI MTS AL MUJAHIDIN 2 SAMARINDA - Azizatun Nisa, Rahmatiana; Eka Wardhana, Kautsar (Universitas Nahdlatul Ulama Kalimantan Timur, 2024)
Situational leadership is a flexible leadership style, where the leader can adjust his leadership approach based on existing conditions and situations. In the madrasah context, integration includes the synergy between management, teaching staff, curriculum, and student development to create a conducive and effective educational environment. The research method used qualitative with a case study approach. Data was collected through in-depth interviews, observation and document analysis. The research results showed that the headmaster of MTs Al Mujahidin 2 Samarinda adopted various leadership styles, such as directing and training employees, participation and authority, based on needs and madrasah development level. Thus, the educational goals are achieved effectively, improving coordination between teaching staff, and synergy in implementing academic programs. The results confirmed that situational leadership has a significant role in supporting integration at MTs Al Mujahidin 2 Samarinda, which impacts the learning quality and madrasah management.